Sovereign Wealth Funds in the Pacific Island Countries : Macro-Fiscal Linkages - Medas, Paulo (IMF Working Papers; Working Paper ;, 2007)
This paper looks at the role Sovereign Wealth Funds have played in the Pacific Island Countries in achieving key macro-fiscal policy objectives, namely, protecting the budget from high revenue volatility and strengthening fiscal prospects. Evidence shows that the funds' effectiveness has been hampered by lack of integration with the budget, institutional weaknesses, and inadequate controls. These factors, together with weak asset management, have sometimes led to substantial financial losses and undermined fiscal policy. Funds, if well designed, could be used as a tool to support a sound fiscal framework, but should not be seen as a substitute for fiscal reforms.